Evolution of Ethical Principles in the Practice of Pharmaceutical Medicine From a UK Perspective - Morris, Thomas; Brostoff, Joshua M.; Stonier, Peter David; Boyd, Alan (Frontiers in Pharmacology, 2020)
Pharmaceutical medicine has evolved to be a distinct medical scientific discipline over time. Pharmaceutical medicine has distinctive features related to complex innovative medicines development activities in an often commercially focused competitive environment. This sometimes uneasy mix of professionalism and commercialisation demands of its medical and scientific researchers alike, a focus on strict adherence to ethical standards, guidelines, practices and behaviours in the interest of delivering new, effective, high-quality lifesaving and life-enhancing medicines quickly and reliably to patients in need. To support the specialty, codes of ethical standards and practices have been developed. These are outlined in this paper along with relevant historical perspectives and interrelationship with concepts of professionalism.